2021
DOI: 10.1111/ijcp.14750
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Vitamin D Levels in the serum of Patients with Postherpetic neuralgia and its correlation to pain severity: A cross‐sectional comparative study

Abstract: Vitamin D is an essential micronutrient for human health. It is a secosteroid (a steroid with a broken ring) known long ago for its role in the musculoskeletal system. Vitamin D's primary function was considered the maintenance of bone and calcium and phosphorus levels in the circulation. However, as time went on, more vitamin D functions were discovered. Its pleiotropic effects on cellular proliferation, differentiation, and the immune system were still a significant field of study. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(92 reference statements)
1
3
0
Order By: Relevance
“…In our study, we found a significant decrease in serum vitamin D levels in patients with PHN, which is consistent with Seetan et al's findings 44 . They stated that low vitamin D levels are associated with the risk of PHN incidence in the elderly with chronic pain.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we found a significant decrease in serum vitamin D levels in patients with PHN, which is consistent with Seetan et al's findings 44 . They stated that low vitamin D levels are associated with the risk of PHN incidence in the elderly with chronic pain.…”
Section: Discussionsupporting
confidence: 93%
“…43 In our study, we found a significant decrease in serum vitamin D levels in patients with PHN, which is consistent with Seetan et al's findings. 44 They stated that low vitamin D levels are associated with the risk of PHN incidence in the elderly with chronic pain. Starting vitamin D supplementation in patients with HZ may reduce the likelihood of subsequent PHN, suggesting that vitamin D may have a protective effect on severe neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67] Insufficient levels of Vitamin D are associated with PHN. 47,68,69 Vitamin D is essential for the growth, survival, and proliferation of neurons, making it a potential therapeutic option for various neurodegenerative diseases. [70][71][72] In patients with HZ, Vitamin D supplementation may reduce the likelihood of subsequent PHN, indicating that it could have a protective effect against severe neuroinflammation 47,73,74 Lastly, in their study, Oskay et al discovered that there is a significant positive correlation between the levels of Hcy in severe HZ rashes and the development of PHN.…”
Section: Dovepressmentioning
confidence: 99%
“…Vitamin D is a steroid, functioning as a hormone in the human body and having a role in glucose homeostasis and sensitivity to insulin There was evidence for an association between lower serum 25(OH)D levels and higher prevalence of DPN in individuals with obesity [46]; however, there was no evidence to support the causal association of serum 25(OH)D levels with diabetic neuropathy [47]. Studies also indicated important roles of vitamin D in postherpetic neuralgia (PHN) [48], multiple myeloma [49], CIPN [50], carpal tunnel syndrome (CTS) [50], and plexiform neurofibromas (PNFs) [51]. Patients with these diseases have high prevalence of vitamin D deficiency.…”
Section: Vitamin Dmentioning
confidence: 99%